Effects of ractopamine (paylean) dose and feeding duration on pig performance in a commercial finishing facility - R G Main; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
A total of 1,035 gilts were used in a 28- day trial conducted in a commercial research facility to determine the influence of ractopamine (PayleanTM) dose (4.5 or 9.0 g/ton) and feeding duration (7, 14, 21, or 28 days prior to slaughter) on pig performance and carcass composition. Ractopamine supplementation at 4.5 g/ton for 14 to 28 days, and 9 g/ton for 7 to 28 days, improved (P<0.05) ADG by 26 to 35% (0.35 - 0.46 lb/d) and F/G by 16 to 20% (0.64 to 0.79) during the 28-days prior to slaughter. Due to these improvements in growth, carcass weights increased 8 to 10 pounds over controls. Fat depth and lean percentage improved (linear, P<0.01) with increased feeding duration. Ractopamine dose did not affect carcass lean parameters. However, carcass yield improved (P<005) when ractopamine was fed at 9.0 g/ton. Feed cost per pound of gain increased (P<0.01) with increasing feeding duration for Paylean and was greater (P<0.05) for pigs fed the 9.0 g/ton dose for 28 days as compared to the control. However, feeding ractopamine at 4.5 g/ton for 14 to 28 days and 9 g/ton for 7 to 28 days improved income over feed costs by 3.53 to 4.76 per head compared to pigs fed the control diet. Return over feed costs improved due to the increased carcass weights and improved feed efficiency with the greatest values achieved with a 14 to 21 day feeding duration. These data indicate feeding ractopamine at either 4.5 or 9.0 g/ton for 14 to 21 days prior to slaughter is a cost-effective strategy to optimize return while minimizing increases in feed cost per pound of gain.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Swine; Ractopamine; Paylean; Economics